THE USE OF PEDAGOGICAL DIAGNOSTICS IN THE DEVELOPMENT OF ANALYTICAL OBSERVATION SKILLS IN STUDENTS (Conferencea, 2023)
This paper explores the application of pedagogical diagnostics as a potent tool in enhancing students' analytical observation skills. Analytical observation is a fundamental cognitive skill that fosters critical thinking and problem-solving abilities. Through the systematic use of diagnostic assessments, educators can gain valuable insights into individual students' strengths and weaknesses in this area. By tailoring instructional strategies to address these specific needs, educators can effectively cultivate and refine students' analytical observation skills. This paper delves into the theoretical underpinnings of pedagogical diagnostics, highlights its practical implementation in educational settings, and presents evidence of its impact on students' cognitive development. The findings underscore the importance of utilizing pedagogical diagnostics as a means to empower students with the essential skill of analytical observation.